The Real and Financial Implications of Corporate Hedging - CAMPELLO, MURILLO; LIN, CHEN; MA, YUE; ZOU, HONG (Journal of Finance, 2011)
ABSTRACT We study the implications of hedging for corporate financing and investment. We do so using an extensive, hand‐collected data set on corporate hedging activities. Hedging can lower the odds of negative realizations, thereby reducing the expected costs of financial distress. In theory, this should ease a firm's access to credit. Using a tax‐based instrumental variable approach, we show that hedgers pay lower interest spreads and are less likely to have capital expenditure restrictions in their loan agreements. These favorable financing terms, in turn, allow hedgers to invest more. Our tests characterize two exact channels—cost of borrowing and investment restrictions—through which hedging affects corporate outcomes. The analysis shows that hedging has a first‐order effect on firm financing and investment, and provides new insights into how hedging affects corporate value. More broadly, our study contributes novel evidence on the real consequences of financial contracting.